A Novel Low-Risk Germline Variant in the SH2 Domain of the SRC Gene Affects Multiple Pathways in Familial Colorectal Cancer - Skopelitou, Diamanto; Miao, Beiping; Srivastava, Aayushi; Kumar, Abhishek; Kuświk, Magdalena; Dymerska, Dagmara; Paramasivam, Nagarajan; Schlesner, Matthias; Lubiński, Jan; Hemminki, Kari; Försti, Asta; Bandapalli, Obul Reddy (Journal of personalized medicine, 2021)
Colorectal cancer (CRC) shows one of the largest proportions of familial cases among different malignancies, but only 5-10% of all CRC cases are linked to mutations in established predisposition genes. Thus, familial CRC constitutes a promising target for the identification of novel, high- to moderate-penetrance germline variants underlying cancer susceptibility by next generation sequencing. In this study, we performed whole genome sequencing on three members of a family with CRC aggregation. Subsequent integrative in silico analysis using our in-house developed variant prioritization pipeline resulted in the identification of a novel germline missense variant in the SRC gene (V177M), a proto-oncogene highly upregulated in CRC. Functional validation experiments in HT-29 cells showed that introduction of SRCV177M resulted in increased cell proliferation and enhanced protein expression of phospho-SRC (Y419), a potential marker for SRC activity. Upregulation of paxillin, β-Catenin, and STAT3 mRNA levels, increased levels of phospho-ERK, CREB, and CCND1 proteins and downregulation of the tumor suppressor p53 further proposed the activation of several pathways due to the SRCV177M variant. The findings of our pedigree-based study contribute to the exploration of the genetic background of familial CRC and bring insights into the molecular basis of upregulated SRC activity and downstream pathways in colorectal carcinogenesis.